Utilización de columnas verticales de filtración de manta y arena como pre-tratamiento de un sistema de filtración lenta - Tangerino, Edson Pereira [UNESP]; Tavares, Marcelo Botini [UNESP]; Ortiz, Iván Andrés Sánchez (My University, 2012)
Slow sand filtration is an efficient water treatment technique used for treating surface water with relatively low levels of contamination. Despite the slow sand filtration at pathogen, algae and cyanobacteria removal efficiency, it has some restrictions in relation to the required area for slow filters, and the cleaning activities for the filters and the stone pre-filters when used in the treatment. This research evaluated during 120 days the use of non woven & sand pre-filtration columns as part of a slow filtration process for the apparent color, turbidity, algae, cyanobacteria, phytoflagellates and diatomaceous. The columns shown an efficient removal of the monitored parameters and demonstrated as a vantage their faster and easier cleaning process and less awkward than the required to the stone pre-filters. The turbidity removal efficiency increased progressively during the experiment, especially after the first 35 days of the start; the apparent color removal by the pre-filtration columns was of 85%, and working together with the polishing of activated carbon columns was up to 95; the diatomaceous, phytoflagellates, algae and cyanobacteria removal by the columns achieve a weekly average of 95%, it's recommended to use filtration rates lower to 1,5m 3/m 2/d.
Synthetic non-woven fabrics & sand vertical filtration columns as a slow filtration pre-treatment system
Keywords: Multiple-stage filtration; Pre-filtration vertical columns; Slow filtration; Water treatment